(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The current world is observing huge developments in presenting the opportunity for organizations and administrative units to use information and communication technology and their adoption by administrative work due to its importance in the achievement of work with higher efficiency, speed, and facility of communication with all individuals and companies using various means of communication Depending on the Internet networks. Therefore, the research dealt with the study of electronic systems designed and adopted in the creation or construction of a database for archiving data, which is the main method in organizations and administrative units in developed countries. Where this system works to convert documents, and manual processes and their attachments to The research was based on the design of an electronic system in the Tax Audit and Examination Section to archive taxpayers’ data and save it in a database using the Microsoft Excel spreadsheet program, and then create an e-mail helps in communicating with the department electronically for easy access to the data to be audited, and easy to save within the system and quick access at any time. The most important findings reached are the importance of electronic data archiving and protection from hazards that may occur. This was not limited to a certain organization or administrative unit, but involves all organizations, both governmental and non-governmental and also tax departments in all its sections, especially the Tax Audit and Examination Section, because it represents the core work of the tax administration in achieving tax justice to ensure the precision of results of taxpayers’ accounts. Taking into consideration the need to design electronic systems that help in archiving and documenting data in an adjustable manner to include work in the Department of Information and Communication Technology and the design of electronic systems that help in archiving and documenting data in an adjustable manner According to developments and variations in the work. A special e-mail should be created for the department to make it easier for the taxpayers to communicate and provide data in electronic and direct form